PENINGKATAN KEMAMPUAN MOTORIK KASAR ANAK USIA DINI MELALUI KEGIATAN TARI BEBEK DI TK ASSALAM SURABAYA - Ayu Indah Wilasti; Muchamad Arif (Universitas Narotama, 2026)
This study aims to improve the gross motor skills of early childhood through duck dance activities at Assalam Kindergarten Surabaya. This study was motivated by the low gross motor skills of children in group B, especially in the aspects of motor coordination, balance, agility, flexibility, and the ability to adjust body movements to the rhythm of music. The research method used was Classroom Action Research (CAR) which was carried out in three cycles. Each cycle consisted of planning, action implementation, observation, and reflection. The subjects of the study were 15 children in group B of Assalam Kindergarten Surabaya. Data collection techniques were carried out through structured observation, documentation, and performance assessment based on children's gross motor indicators. Data analysis techniques used quantitative descriptive analysis by calculating the percentage of children's gross motor development in each cycle. The results showed that duck dance activities can improve children's gross motor skills. In the pre-cycle, children's achievements were still low, namely 27% in the first indicator, 13% in the second indicator, and 20% in the third indicator. After the action was carried out, the results increased in the first cycle to 40%, 27%, and 33%. In cycle II, improvements were seen at 53%, 47%, and 60%. Furthermore, in cycle III, children's gross motor skills increased to 80% in the first indicator, 87% in the second indicator, and 93% in the third indicator. These results indicate that the duck dance activity can improve children's gross motor skills because the movements are simple, repetitive, and fun, and involve hand and foot coordination, body balance, and adjustment of movements to the rhythm of the music. Thus, the duck dance activity can be used as an effective alternative learning activity to stimulate gross motor development in early childhood. Keywords: gross motor skills, duck dance, early childhood, classroom action research